Charakterisierung von Bariumstrontiumtitanat‐Partikeln mithilfe der Röntgenbeugung. Issue 3 (27th January 2014) - Herrmann, Michael; Förter‐Barth, Ulrich; Roßmann, Christian; Teipel, Ulrich; Teipel, Ulrich; Weber, Alfred
<x xml:space="preserve">Abstract</x> Nanoscale ferroelectric ceramics are promising materials for the development of miniaturized components for the semiconductor industry. The dispersion of barium strontium titanate (BST) for use in integrated thin film capacitors was investigated. X‐ray diffraction revealed important information on the structure of the BST and the change it undergoes during the dispersion process. Crystallite size, the presence of a two‐phase system, and the stoichiometry may affect the dielectric properties of the BST and its future applications, and has to be considered in development and quality assurance.